A sociologia e a escola em debate nos Encontros Nacionais sobre o Ensino de Sociologia na Educação Básica - Danyelle Nilin Gonçalves (Ciências Sociais Unisinos)
Created as a space of reflection, training and sharing of learning experiences, research and modes of implementation of sociology in the curriculum of Brazilian states, the National Meetings on the Teaching of Sociology in Basic Education (ENESEB) cannot be understood without taking into account the implementation of Sociology in the Brazilian high school curriculum. As sociology was becoming institutionalized in school and new topics began to be dealt with in classrooms, these issues became part of the discussions at those events, the focus of educational workshops, presentations in posters, oral communications in work groups and round tables. This article deals with the significance of this meeting, its political and educational dimensions in the sense of belonging, visibility, struggle, sociability, knowledge dissemination, discussion and debate.